Designing Brand Guidelines, Content Pillars, and Content Calendar for UMKM Social Media Using Design Thinking Method - Eliana Johana Rebecca; Muhammad Aqshel Revinzky (International Journal of Economics Accounting and Management, 2024)
Internet users in the era of digitalization are increasing day by day, including UMKM who are also developing, especially in Indonesia. The internet is used as a means of buying and selling, especially through social media. In encouraging sales, UMKM also often use social media as a promotional medium to introduce their products to the wider public or potential buyers. UMKM Anne Klappertaart is one of the UMKM that uses Instagram social media for sales and promotions. However, knowledge and skills in using social media that are not yet optimal mean that promotional efforts via UMKM social media do not run effectively. In this thesis the author uses a qualitative research method by utilizing the Design Thinking method. This research shows that it is important to create brand guidelines and content pillars to make UMKM content more targeted and in line with consumer tastes so that they are interested in viewing and buying UMKM products. Apart from that, it is important to use a content calendar so that the uploaded content does not overlap with one other content. Therefore, the use of brand guidelines, content pillars and content calendars makes it easier for UMKM Anne Klappertaart to manage social media so that in the future Anne Klappertaart can create content independently